Plant Genes Benefitting Aphids—Potential for Exploitation in Resistance Breeding - Åhman, Inger; Kim, Sung-Yong; Zhu, Li-Hua (Frontiers in Plant Science, 2019)
Aphids are phloem sap-feeding insects common as pests in various crops. Many of the omics studies reviewed in this article interpret plant responses to aphids as plant defence induction, but here we emphasize how aphids may manipulate the plants to make them more suitable as hosts, i.e. more susceptible. Our aim is to try to reveal host plant susceptibility (S) genes, knowledge which can be exploited for making a plant more resistant to its pest by using new plant breeding techniques to knock out or down such S genes. S genes may be of two types, those that are involved in reducing functional plant defence and those involved in increasing plant factors that are positive to the aphid. Approximately 40% of the omics studies we have reviewed indicate how aphids may modify their host to their advantage. Aphids may manipulate their hosts so that a type of plant defence is induced that the aphid is tolerant to. To improve food quality, aphids may influence regulation of nutrient transport-related genes and thereby make the phloem sap richer in amino acids. Furthermore, in order to facilitate the access to phloem sap, aphids may regulate genes to help loosen plant cell walls and to reduce damage-induced callose in sieve elements. Phloem feeding by aphids is passive, i.e. dependant on sap turgor. Aphid-induced changes in ABA signalling and regulation of turgor-related genes is another way for aphids to increase access to nutrients. To exploit knowledge obtained so far, we suggest that genome editing CRISPR/Cas9 or RNA interference techniques are applied in crops to study if the effect is sufficient to keep the aphid pest at economically viable levels and without severe pleiotropic effects. As a complement, we also propose functional studies of known recessively inherited resistance discovered in some aphid-crop combinations, to potentially identify new types of S genes that later could be knocked out or down also in other crops to improve their resistance to aphids.